Normalisation of impoliteness or moral panic? On expressing aversion to children on the Internet - Bańczyk, Emilia (Papers in Linguistics, 2024)
The article is concerned with the linguistic expression of dislike directed at children on the Internet. Discourse linguistics is employed to analyse statements from a Facebook page Nie lubię dzieci [“I don’t like children”] as an illustration of the problem. The proposed case study is a starting point for further considerations on expressing resentment towards children in the context of concepts such as: moral panic, normalisation of impoliteness and shamelessness, as well as discrimination. The author perceives expressing aversion to children openly as a threat to the integrity of society.